AI‐Controlled Robot Masks: Resisting Patriarchal Oppression. (7th April 2022) - Farahi, Behnaz
Abstract: Using computational techniques to foster new empathetic relationships between human bodies and the space around them, Behnaz Farahi, Assistant Professor in the Department of Design at the California State University in Long Beach, presents some of the concepts and events that have inspired her research and focuses on a recent project for an interactive niqab.